Analysis of The Role of Customer Service in Improving Service Quality at Bank Rakyat Indonesia Takalala Unit Soppeng DistricTt - Fitriandini, Fitriandini; Rivai, Andi Muhammad; Kasmita, Maya (Pinisi Business Administration Review, 2023)
Improving the service quality of Bank Rakyat Indonesia Takalala Unit, Soppeng Regency is one way for banks to remain competitive in the banking market share. Customer service plays an important role in improving the quality of service in a bank because the quality of service provided by customer service determines the bank's image.The problem that then arises is what is the role of customer service and the determinant factors that influence the quality of service at that location. To achieve this goal, data collection techniques are used through observation, interviews, and documentation. Data is processed using descriptive qualitative. The results showed that the role of customer service in improving service quality includes paying attention to the completeness of facilities, completing customer needs, handling customer requests and complaints, establishing good relations, and maintaining the confidentiality of customer data. Furthermore, the determinant factors that affect service quality are service quality, cooperation network, customer convenience, alternative transactions, good relations, customer empowerment, socialization and technology assistance, service consistency, and alternative socialization.